Contribution of live fences to control the heat stress in dairy cows in the humid tropic of Costa Rica - Argeñal Vega, Pedro R. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Mag. Sc) -- CATIE, Turrialba (Costa Rica),2011